2012
DOI: 10.1021/jm300652f
|View full text |Cite
|
Sign up to set email alerts
|

α-Substituted β-Oxa Isosteres of Fosmidomycin: Synthesis and Biological Evaluation

Abstract: Specific inhibition of enzymes of the non-mevalonate pathway is a promising strategy for the development of novel antiplasmodial drugs. α-Aryl-substituted β-oxa isosteres of fosmidomycin with a reverse orientation of the hydroxamic acid group were synthesized and evaluated for their inhibitory activity against recombinant 1-deoxy-d-xylulose 5-phosphate reductoisomerase (IspC) of Plasmodium falciparum and for their in vitro antiplasmodial activity against chloroquine-sensitive and resistant strains of P. fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…It is possible that fosmidomycin penetrates cells adequately of itself. The most recent studies reported a series of fosmidomycin analogs with enhanced potency against the purified enzyme and growth of the Plasmodium parasite in vitro [219]. While the activity was somewhat enhanced by bis-POM protection, the results parallel findings of limited activity of the tri-POM pro-drug squalene synthase inhibitor ER27856 in Leishmania .…”
Section: Current Applications Of Prodrug Technologymentioning
confidence: 84%
“…It is possible that fosmidomycin penetrates cells adequately of itself. The most recent studies reported a series of fosmidomycin analogs with enhanced potency against the purified enzyme and growth of the Plasmodium parasite in vitro [219]. While the activity was somewhat enhanced by bis-POM protection, the results parallel findings of limited activity of the tri-POM pro-drug squalene synthase inhibitor ER27856 in Leishmania .…”
Section: Current Applications Of Prodrug Technologymentioning
confidence: 84%
“…α -Aryl-substituted β -oxa isosteres of fosmidomycin with a reverse orientation of the hydroxamic acid group were synthesized and evaluated for their inhibitory activity against recombinant 1-deoxy-d-xylulose 5-phosphate reductoisomerase (IspC) of Plasmodium falciparum and for their in vitro antiplasmodial activity against chloroquine-sensitive and resistant strains of P. falciparum . The most active derivative inhibits IspC protein of P. falciparum ( Pf IspC) with an IC 50 value of 12 nM and shows potent in vitro antiplasmodial activity [40]. …”
Section: Antimalarial Compounds Against Isoprenoid Biosynthetic Pamentioning
confidence: 99%
“…Behrendt et al ( 2011 ) synthesized the reverse hydroxamate based inhibitors amongst which [1-(3,4-Difluorophenyl)-4-(hydroxylamino)-4-oxobutyl] phosphonic acid is considered most effective with an IC 50 of 3 nM. Later Brücher et al ( 2012 ) synthesized α-Aryl-substituted β-oxa isosteres of Fos with a reverse orientation of the hydroxamic acid group and tested them against recombinant P. falciparum IspC and chloroquine-sensitive and resistant strains of P. falciparum . They found an inhibitory activity of these derivatives against P. falciparum IspC, with the most active derivative ((3,4-Difluorophenyl) (2-(hydroxy(methyl)amino)-2-oxoethoxy) methyl) phosphonic acid showing an IC 50 value of 12 nM and potent in-vitro anti-plasmodial activity.…”
Section: Introductionmentioning
confidence: 99%